Transmission of reduced levels of miR-34/449 from sperm to preimplantation embryos is a key step in the transgenerational epigenetic inheritance of the effects of paternal chronic social instability stress - Alexandre Champroux; Yang Tang; David A. Dickson; Alice Meng; Anne Harrington; Lucy Liaw; Matteo Marzi; Francesco Nicassio; Thorsten M. Schlaeger; Larry A. Feig (Epigenetics)
The transgenerational effects of exposing male mice to chronic social instability (CSI) stress are associated with decreased sperm levels of multiple members of the miR-34/449 family that persist after their mating through preimplantation embryo (PIE) development. Here we demonstrate the importance of these miRNA changes by showing that restoring miR-34c levels in PIEs derived from CSI stressed males prevents elevated anxiety and defective sociability normally found specifically in their adult female offspring. It also restores, at least partially, levels of sperm miR-34/449 normally reduced in their male offspring who transmit these sex-specific traits to their offspring. Strikingly, these experiments also revealed that inducing miR-34c levels in PIEs enhances the expression of its own gene and that of miR-449 in these cells. The same induction of embryo miR-34/449 gene expression likely occurs after sperm-derived miR-34c is introduced into oocytes upon fertilization. Thus, suppression of this miRNA amplification system when sperm miR-34c levels are reduced in CSI stressed mice can explain how a comparable fold-suppression of miR-34/449 levels can be found in PIEs derived from them, despite sperm containing ~50-fold lower levels of these miRNAs than those already present in PIEs. We previously found that men exposed to early life trauma also display reduced sperm levels of miR-34/449. And here we show that miR-34c can also increase the expression of its own gene, and that of miR-449 in human embryonic stem cells, suggesting that human PIEs derived from men with low sperm miR-34/449 levels may also contain this potentially harmful defect.